BS EN 3660-004. Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Part 004. Cable outlet, style A, straight, unsealed with clamp strain relief. Product standard (17th January 2020) - British Standards Institution,
No abstract available